Charge transfer in dissociating iodomethane and fluoromethane molecules ionized by intense femtosecond X-ray pulses - Boll, R.; Erk, B.; Coffee, R.; Trippel, S.; Kierspel, T.; Bomme, C.; Bozek, J. D.; Burkett, M.; Carron, S.; Ferguson, K. R.; Foucar, L.; Küpper, J.; et al. (My University, 2016)
Ultrafast electron transfer in dissociating iodomethane and fluoromethane molecules was studied at the Linac Coherent Light Source free-electron laser using an ultraviolet-pump, X-ray-probe scheme. The results for both molecules are discussed with respect to the nature of their UV excitation and different chemical properties. Signatures of long-distance intramolecular charge transfer are observed for both species, and a quantitative analysis of its distance dependence in iodomethane is carried out for charge states up to I21+. The reconstructed critical distances for electron transfer are in good agreement with a classical over-the-barrier model and with an earlier experiment employing a near-infrared pump pulse. © 2016 Author(s).
Citation: Boll, R., Erk, B., Coffee, R., Trippel, S., Kierspel, T., Bomme, C., . . . Rudenko, A. (2016). Charge transfer in dissociating iodomethane and fluoromethane molecules ionized by intense femtosecond X-ray pulses. Structural Dynamics, 3(4). doi:10.1063/1.4944344
Additional Authors: Marchenko, T.;Miron, C.;Patanen, M.;Osipov, T.;Schorb, S.;Simon, M.;Swiggers, M.;Techert, S.;Ueda, K.;Bostedt, C.;Rolles, D.;Rudenko, A.